2021
DOI: 10.3389/fneur.2021.662235
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenin in the Neurogenic Subventricular Zone After Stroke

Abstract: Ischemic stroke is a leading cause of death and disability worldwide with effective acute thrombolytic treatments. However, brain repair mechanisms related to spontaneous or rehabilitation-induced recovery are still under investigation, and little is known about the molecules involved. The present study examines the potential role of angiogenin (ANG), a known regulator of cell function and metabolism linked to neurological disorders, focusing in the neurogenic subventricular zone (SVZ). Angiogenin expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…It has been suggested that adult neurogenesis is altered in ALS-FTD [60]. ANG is also upregulated during adult neurogenesis in mice [61] and is expressed in the mouse subventricular zone after ischaemic stroke in the neuroblasts [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that adult neurogenesis is altered in ALS-FTD [60]. ANG is also upregulated during adult neurogenesis in mice [61] and is expressed in the mouse subventricular zone after ischaemic stroke in the neuroblasts [34].…”
Section: Discussionmentioning
confidence: 99%
“…ANG is expressed in the developing mouse nervous system and has been shown to play a role in neuronal differentiation of mouse pluripotent cells, as well as in the developing zebrafish nervous system [1,2,30]. It is also expressed in the adult mouse subventricular zone and is implicated in neurogenesis during recovery from stroke [33,34]. Here we asked if ANG played a similar a role during neurogenesis using a human induced pluripotent stem cell (iPSC)‐derived model.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, new neurons are produced in the SVZ around the ventricle and the SGZ in the hippocampus, where neurogenesis occurs most actively and continuously [ 25 , 26 ]. Many studies have shown that when the brain is abnormal, the dividing neuroblasts move to the lesion location, and the migrated cells surround the lesion and slow its progression [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in this previous study, experiments in pre-clinical stroke models also described an ANG increase in the ischemic site when performing task-specific exercise, suggesting an association between rehabilitation and molecular changes in the brain. Moreover, another pre-clinical study from our group has recently described that physical exercise rapidly increased the amount of endogenous ANG in the ipsilateral neurogenic subventricular zone after cerebral ischemia ( 40 ). All this evidence points to potential connections between ANG, stroke disease, and rehabilitation, although confirmatory investigations are needed.…”
Section: Discussionmentioning
confidence: 99%